Density functional theory-based cluster expansion to simulate thermal annealing in FeCrW alloys. Issue 5 (11th February 2017) - Bonny, G.; Castin, N.; Domain, C.; Olsson, P.; Verreyken, B.; Pascuet, M. I.; Terentyev, D.
Abstract: In this work, we develop a rigid lattice cluster expansion as an ultimate goal to track the micro-structural evolution of Eurofer steel under neutron irradiation. The fact that all (defect) structures are mapped upon a rigid lattice allows a simplified computation and fitting procedure, thus enabling alloys of large chemical complexity to be modelled. As a first step towards the chemical complexity of Eurofer steels, we develop a cluster expansion (CE) for the FeCrW-vacancy system based on density functional theory (DFT) calculations in the dilute alloy limit. The DFT calculations suggest that only CrW clusters containing vacancies are stabilised. The cluster expansion was used to simulate thermal annealing in Fe–20Cr– x W alloys at 773 K. It is found that the addition of W to the alloy results in a non-linear decrease in the precipitation kinetics. The CE was found suitable to describe the energetics of the FeCrW-vacancy system in the Fe-rich limit.